Qatar : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Qatar. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights the adverse impact of lower hydrocarbon prices on the macroeconomic performance of Qatar. Growth has slowed despite still-resilient nonhydrocarbon activity. Real GDP growth of 2.7 percent is estimated for 2016. Inflation remained low despite subsidy cuts, averaging about 2.7 percent in 2016. Growth is expected to slow in the medium term as public investment growth tapers off and hydrocarbon output continues to slow. Further subsidy cuts, a moderate recovery in global commodity prices, and the introduction of a value-added tax are expected to improve the fiscal and external balances gradually over the near to medium term.